EFFICACY OF PROBIOTICS AND ESSENTIAL OILS AS ALTERNATIVES TO ANTIBIOTIC GROWTH PROMOTERS IN BROILER CHICKENS - W. M. Al-Younes; A. M. Abdelqader; M. KH. Abuajamieh; K. O. Nassar (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
The current study was carried out on broiler chickens to assess whether probiotics or essential oils could be utilized instead of antibiotics growth promoters (AGP) in typical feed formulations, to determine their effectiveness. A total of 2250 broiler chicks at one-day old age were allocated into 5 dietary treatments in a completely randomized design with 9 replicates per treatment and 50 chicks/replicate. The Probiotic included three strains of Bacillus amyloliquefaciens, the essential oil (EO) was a blend of Cinnamaldehyde-Thymol, and the AGP was Lincomycin™. These additives were added to the basal diets (BD) to formulate the following dietary treatments (T): (T1) control-fed BD that is regularly used by broiler farmers (T2) control-fed BD that is regularly used by broiler farmers and supplemented with Lincomycin™ (100 g/ton) as AGP; (T3) fed BD + Probiotics (Enviva® PRO 60 g/ton); (T4) fed BD + EO (Enviva® 100g/ton); and (T5) fed BD + combination of both probiotics and EO with the same doses used in T3 and T4. The study findings demonstrated that the use of probiotics or essential oils did not have any significant impact on the average body weight gain, final body weight, feed conversion ratio, or footpad lesion scores when compared to the AGP group. It was concluded that replacing the AGP with probiotics or EO, as natural feed additives, had no negative effects on broiler performance. The probiotic strains or the EO could be safe alternatives to AGP.